Social Capital in Mitigating Flood Disaster in the People of Aceh Tenggara, Indonesia - Santi, Hikmah; Ginting, Bengkel; Sitorus, Henry; Ismail, Rizabuana; Manurung, Ria (Open Access Indonesia Journal of Social Sciences, 2022)
The objective of this research was to analyze and discuss the social capital owned by the community in Aceh Tenggara in mitigating flood disasters. The research used the descriptive qualitative method. Our study revealed social capital owned by the community in Aceh Tenggara could help mitigate flood disasters. Cooperation among the central government, the regional government, and the local people seemed to be very good. It was performed commencing from helping the people in the post-incidence of the flood until its mitigation plan. The Cooperation has eventually established trust in the local people and the government that was involved in the policymaking, relocation activity, and distribution to the flood victims. The use of the values of people's local wisdom, such as 'Pelengakhi' (working together) by the local people, helped the flood victims. They also helped spread information about the flood through mosque loudspeakers. This social capital has become a collective strength owned by the local people in mitigating flood disasters.